Fhb1 disease resistance QTL does not exacerbate wheat grain protein loss at elevated CO2 - Hay, William T.; Anderson, James A.; Garvin, David F.; McCormick, Susan P.; Vaughan, Martha M. (Frontiers in Plant Science, 2022)
Fusarium head blight, a devastating cereal crop disease, can cause significant yield losses and contaminate grain with hazardous fungal toxins. Concerningly, recent evidence indicates that substantial grain protein content loss is likely to occur in wheat that is moderately resistant to head blight when it is grown at elevated CO2. Although wheat breeders in North America utilize a number of resistance sources and genes to reduce pathogen damage, the Fhb1 gene is widely deployed. To determine whether Fhb1 is associated with the protein content loss at elevated CO2, twelve near-isogenic spring wheat lines from either a susceptible or moderately susceptible genetic background, and with, or without the Fhb1 QTL, were grown at ambient and elevated CO2 conditions. The near-isogenic lines were evaluated for differences in physiology, productivity, and grain protein content. Our results showed that the Fhb1 QTL did not have any significant effect on plant growth, development, yield, or grain protein content at ambient or elevated CO2. Therefore, other factors in the moderately susceptible wheat genetic background are likely responsible for the more severe grain protein loss at elevated CO2.